The relationship between pre-mir-146a G/C polymorphism and risk of gastric cancer in patients with gastric cancer in Ardabil province, Iran - R., Moradpour Hesari; M., Damandan; S., Hosseini-Asl (International Journal of Advances in Medicine, 2017)
Background: MicroRNAs (miRNAs) are endogenous non-protein-coding short RNAs of 21-23 nucleotides (Kim, 2005; Bartel, 2004).polymorphism in human pre-mir-146a has been recently implicated in human cancers. Gastric cancer (GC) is the most of common cancers, and is especially common in Ardabil province, located in North-West Iran. Single nucleotide polymorphism (SNP)is the most common type of genetic variation in the human genome .polymorphisms in human pre-mi RNA genome lesion modify the processing and/or target selection of human mi RNAs, which are implicated in cell cycle regulation , and thereby play critical roles in carcinogenesis. Pre-mir-146a G/C polymorphism designated rs2910164 is located on chromosome 5, in the stem region opposite to the mature pre-mir-146a sequence. Methods: We performed a hospital-based, case-control study using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method in 100 individuals (50 gastric cancer patients and 50 age and sex matched cancer – free controls). The frequency of genotypes was 9(18%), 17(34%), and 24(48%) among cases and 3(6%), 14(28%), and 33(66%) among controls for C/C, G/C, and G/G, respectively. The 147bp amplified fragment was digested by Sac1 (Thermo science co.). An uncut fragment indicates allele G. However, substitution of C allele by G allele tends to create a Sac1 restriction site. Therefore, C allele is observed by 122bp and 25bp digested products. If the quantity of restriction enzyme used is inadequate, the homozygous may be detected as heterozygote, therefore, some sequenced samples were chosen for evaluating the accuracy of digestion. All the statistical analyses were performed using spss software. Results: The frequencies of pre-miR-146a G/C genotypes in the case groups were significantly different from those in the control groups although clinically CC genotype in patients with gastric cancer incidence was higher than the control groups (18% versus 6%), so this difference was statistically significant (p=0.038). Conclusions: In this study, between the polymorphism of G/C hsa-mir-146a and the risk of gastric cancer in Ardabil province, a significant relationship was found.